2016
DOI: 10.1016/j.bandc.2016.05.008
|View full text |Cite
|
Sign up to set email alerts
|

The effect of interference on temporal order memory in individuals with Parkinson’s disease

Abstract: Memory for the temporal order of items or events in a sequence has been shown to be impaired in older adults and individuals with Parkinson’s disease (PD). The present study examined the effects of high and low interference on temporal order memory in individuals diagnosed with PD (n = 20) and demographically similar healthy older adults (n = 20) utilizing a computerized task used in previously published studies. During the sample phase of each trial, a series of eight circles were randomly presented one at a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…It is of interest that only the TLE group seemed to rely partially on spatial working memory abilities to complete the task. Previous studies have shown an association between poorer spatial working memory and poorer pattern separation performance under high levels of interference in older adults (DeFord, et al, 2016). Notably, although there were trends between pattern separation performance and a test of basic visuospatial processing, these associations were not significant, therefore, visuospatial processing was not driving pattern separation performance.…”
Section: 4 Discussionmentioning
confidence: 96%
“…It is of interest that only the TLE group seemed to rely partially on spatial working memory abilities to complete the task. Previous studies have shown an association between poorer spatial working memory and poorer pattern separation performance under high levels of interference in older adults (DeFord, et al, 2016). Notably, although there were trends between pattern separation performance and a test of basic visuospatial processing, these associations were not significant, therefore, visuospatial processing was not driving pattern separation performance.…”
Section: 4 Discussionmentioning
confidence: 96%
“…Prospective memory deficits have been consistently reported in PD without dementia and may be attributable to associated frontal system dysfunction (Costa, Peppe, Caltagirone, & Carlesimo, 2008, 2013; Foster, McDaniel, Repovš, & Hershey, 2009; Ramanan & Kumar, 2013). There is also evidence of poorer temporal order memory (e.g., sequence of events or activities) and content memory (e.g., the actual event or activity) performances in nondemented PD compared to healthy controls (DeFord et al, 2016; McAlister & Schmitter-Edgecombe, 2016). Temporal ordering, or the ability to plan and execute a sequence of steps, is important for performing daily activities.…”
mentioning
confidence: 99%